Genres of Listening : An Ethnography of Psychoanalysis in Buenos Aires - Marsilli-Vargas, Xochiquetzal, 1977- (Book collections on Project MUSE., 2022)
"Genres of Listening explores a unique culture of listening and communicating in Buenos Aires, Argentina. Xochiquetzal Marsilli-Vargas shows how psychoanalytic listening (which is grounded in the fundamental formula, "When you say X, I hear Y") has become a therapeutic technology that has crossed from the clinical setting to become a central element of social interaction and cultural production in Buenos Aires, the city with the highest number of practicing psychologists and psychoanalysts in the world. Marsilli-Vargas' fieldwork shows that "the lay listener in Buenos Aires who translates the words of others into new interpretations is helping the person to listen to herself." Ultimately, Genres of Listening suggests that there could be other "genres" of listening, such as ethical listening, which have been vastly underexplored"--